Retrospective analysis of pregnancies at the Grootte Schuur Hospital : a comparison of pregnancy outcomes in pre-gestational and gestational diabetes - Ekpebegh, Chukwuma Ogbonna (Division of Endocrinology and Diabetology, 2014)
Includes bibliographical references (leaves 67-80).